The photo-electrical performance of the novel CuAlMnFe shape memory alloy film in the diode application - Canbay, C. Aksu; Tataroglu, A.; Dere, A.; Al-Sehemi, Abdullah G.; Karabulut, Abdulkerim; Bektas, A.; Yakuphanoğlu, Fahrettin (Elsevier, 2021)
In this study, the Cu-Al-Mn-Fe shape memory alloy (SMA) was prepared using arc melting technique. The alloy was examined with help of X-ray diffraction (XRD) and differential scanning calorimetry (DSC) methods. We fabricated Cu-Al-Mn-Fe/n-Si diode by forming the shape memory alloy thin film on n-type silicon. The current-voltage (I-V) measurement of the diode was carried out under different intensities of illumination. The reverse bias current value of the diode under light was found to be greater than the dark condition. The obtained result shows that the diode displays a photoconducting feature. The main electrical parameters of the structure were obtained from the conventional I-V and Norde method. Besides, the transient photocurrent (TPC) measurement was performed under the various illumination intensity conditions. In addition to these experiments, the measurements of the conductance/capacitance-voltage (G/C-V) were carried out at room temperature and different frequencies. It was found that both G and C are quite sensitive to frequency.
Keywords: Shape memory alloy; Cu-Al-Mn-Fe; Schottky diode; Illumination intensity; Transient photocurrent; Frequency effect; Solar energy; Energy